1987
DOI: 10.1007/bf01869416
|View full text |Cite
|
Sign up to set email alerts
|

Volume-stimulated, Cl−-dependent K+ efflux is highly expressed in young human red cells containing normal hemoglobin or HbS

Abstract: We report here that a Cl(-)-dependent K+ (K:Cl) efflux, which is stimulated by N-ethylmaleimide (NEM) and by increased red cell volume, exists in young red cells of individuals with normal hemoglobin A (AA) and in those homozygous for hemoglobin S (SS). We have investigated this K:Cl efflux in several density-defined red cell fractions obtained from Percoll-Stractan continuous density gradients. We found high activity of the NEM-stimulated K:Cl transport in reticulocytes and young red cells from nine sickle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(67 citation statements)
references
References 25 publications
3
64
0
Order By: Relevance
“…Calculation of the cotransport fluxes measured in fractionated red cells based on a constant cell number (1013) also showed a statistically significant correlation although the slope of the regression line was reduced (r = -0.629; P _< 0.0017; flux [millimoles per 10 t3 cells] = 1.893 -0.013 x MCV). These results are similar to those reported by Chipperfield and Mangat (1986) and Duhm (1987), but differ from those of Canessa et al (1987), who found no consistent differences in bumetanide-sensitive K efflux between fractions of red cells with different density (and presumably MCVs) from donors with reticulocytosis. The basis for this reported difference with the present results is not clear.…”
Section: Characteristics Of Fractionated Red Cellssupporting
confidence: 89%
“…Calculation of the cotransport fluxes measured in fractionated red cells based on a constant cell number (1013) also showed a statistically significant correlation although the slope of the regression line was reduced (r = -0.629; P _< 0.0017; flux [millimoles per 10 t3 cells] = 1.893 -0.013 x MCV). These results are similar to those reported by Chipperfield and Mangat (1986) and Duhm (1987), but differ from those of Canessa et al (1987), who found no consistent differences in bumetanide-sensitive K efflux between fractions of red cells with different density (and presumably MCVs) from donors with reticulocytosis. The basis for this reported difference with the present results is not clear.…”
Section: Characteristics Of Fractionated Red Cellssupporting
confidence: 89%
“…4 However, Hb S or Hb C in trait RBCs (AS or AC) with normal mean cell age, or after incorporation into normal RBC ghosts, appears to increase KCC activity. 5,6 Expression of Hb S or C in transgenic mice also increases red cell KCC activity.…”
Section: Introductionmentioning
confidence: 99%
“…KCC is active in reticulocytes and diminishes with red cell maturation. 3,4 It is thought to function physiologically to reduce red blood cell (RBC) volume and establish the high cellular hemoglobin concentration (CHC) characteristic of mature cells. KCC is activated in vitro by cell swelling, acid pH, sulfhydryl oxidation/alkylation, and exposure to urea, but the relative importance of these stimuli in vivo is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…17 The KCC is active in reticulocytes, especially sickle reticulocytes, but not in mature RBCs. 18 This pathway is probably not active in older, dense sickle cells.…”
Section: Introductionmentioning
confidence: 99%